2017
DOI: 10.1039/c7sc02621h
|View full text |Cite
|
Sign up to set email alerts
|

Combining the catalytic enantioselective reaction of visible-light-generated radicals with a by-product utilization system

Abstract: We report an unusual reaction design in which a chiral bis-cyclometalated rhodium(iii) complex enables the stereocontrolled chemistry of photo-generated carbon-centered radicals and at the same time catalyzes an enantioselective sulfonyl radical addition to an alkene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…In 2017, Meggers and coauthors reported a different concept in which a prochiral rhodium-coodinated radical intermediate, generated by photoinduced SET, employing Hantzsch ester as photoredox mediator, was reacted with allyl sulfones, providing radical allylation of α,β-unsaturated pyrazoleamides with excellent enantioselectivities (Scheme 47). [67] The utility of this elegant methodology is amplified by a convenient recycling of the by-product sulfonyl radical to form enantioenriched sulfones. The optimised protocol proved to be efficient when applied to a variety of allyl sulfones radical acceptors affording both products 14 and 15 in good to high yields and good to excellent enantioselectivity.…”
Section: Pyrazoleamides In Visible-light-activated Photochemical Reactions 81 Merging Visible Light Photoredox Activation With Asymmetricmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Meggers and coauthors reported a different concept in which a prochiral rhodium-coodinated radical intermediate, generated by photoinduced SET, employing Hantzsch ester as photoredox mediator, was reacted with allyl sulfones, providing radical allylation of α,β-unsaturated pyrazoleamides with excellent enantioselectivities (Scheme 47). [67] The utility of this elegant methodology is amplified by a convenient recycling of the by-product sulfonyl radical to form enantioenriched sulfones. The optimised protocol proved to be efficient when applied to a variety of allyl sulfones radical acceptors affording both products 14 and 15 in good to high yields and good to excellent enantioselectivity.…”
Section: Pyrazoleamides In Visible-light-activated Photochemical Reactions 81 Merging Visible Light Photoredox Activation With Asymmetricmentioning
confidence: 99%
“…In 2017, Meggers and coauthors reported a different concept in which a prochiral rhodium‐coodinated radical intermediate, generated by photoinduced SET, employing Hantzsch ester as photoredox mediator, was reacted with allyl sulfones, providing radical allylation of α,β‐unsaturated pyrazoleamides with excellent enantioselectivities (Scheme 47). [67] …”
Section: Pyrazoleamides In Visible‐light‐activated Photochemical Reactionsmentioning
confidence: 99%
“…Readily available Hantzsch esters were used as the photoredox mediators and chiral bis-cyclometalated rhodium(III) complex induced the stereocontrol in the photogenerated carboncentered radicals. 74 Moreover, Rh-coordinated to the prochiral radicals, created by a selective photoinduced single electron reduction, combines with allyl sulfones 147 in a highly stereocontrolled fashion to form chiral sulfones 149, (Scheme 51). A scope with respect to allyl sulfones 149 was presented.…”
Section: Scheme 50 Sulfonylation Of Vinyl Tosylates 144 and Mechanism Proposalmentioning
confidence: 99%
“…In 2017, Meggers developed a system that allowed the formation of a carbon-centered radical from ,-unsaturated ketones 146 which added with electron-poor allyl sulfones 147 to form the radical allylation products 148 in up to 96% ee and a sulfonyl radical and this byproduct was then utilized in an addition to the ,-unsaturated ketone 146 to give -sulfonyl ketones 149 in up to 89% ee (Scheme 51). 74 Readily available Hantzsch esters (HE) were used as the photoredox mediators and chiral bis-cyclometalated rhodium(III) complex induced the stereocontrol in the photogenerated carbon-centered radicals. Initially, the bidentate coordination of 146 with the Lewis acid forms a LA/substrate complex, which is a much better electron acceptor than the free substrate, and it undergoes selective SET by the visible-light-excited HE (HE*) to generate the key Rh-coordinated radical intermediate a.…”
Section: Review Synthesismentioning
confidence: 99%
“…[5] Moreover,p hotoredox-mediated processes are as amenable to picomole-scale reactions for high-throughput screening [21] as they are to [d] See ref. [26]. [e] See ref.…”
Section: Introductionmentioning
confidence: 99%